UNIVERSITY TRAINING IN PSYCHOLOGY OF RELIGION AND SPIRITUALITY: A NEED OR UTOPIA? - Salgado Lévano, Ana Cecilia (2016)
This theoretical research is positioned within the field of Psychology of Religion and Spirituality. Its goals are to analyze the training received by psychology students in this field, as well as the attitudes of the instructors in charge of such training. Based on research, it is reported that the religious and spiritual dimension is critical in an individual’s development; consequently, it is of outmost importance that future psychologists be prepared to understand the way such variables as faith in God, spiritual well-being, beliefs, convictions and needs, and coping styles, among others, affect the human being. Since most Latin American universities do not offer training courses related to this field, a revision of curricula is suggested, so as to identify gaps in such training and include courses that will enable future psychologists to fully perform their duties.